Have Bologna Process Improved the Master’s Educations standards? An Albanian Employer’s Perspective - Dhamo, Zhaklina Gjergji; Kume, Vasilika (Serbian Journal of Management, 2013)
In this research the professional innovation of the Master studies as per Bologna  Process standards, observed from the possible buyers of such product, the Albanian Employers is studied.With the help of a survey, it has been tried to reflect the opinion of the employers about the quality of a Master degree according to the standarts of the Bologna Process. Around 53% of the employers think that the Bologna system can qualitatively improve the employee’s qualification, but this should be observed in a long-term horizon. About 87% of employers would not pay more a prospective employee given the fact that he/she has earned a master degree according the Bologna Process standards. This individual, in the majority of Albanian companies, would not be considered as more qualified than other colleagues who are educated in another system. Moreover, 20% of employers with work experience 11-15 years believe that the Bologna Process worsens the quality of education in Albania.
Keywords: Personnel Management; Firm Employment Decisions; Albanian Employers; Bologna Process; Higher Education